Development of biometric identification using system neural networks - Hrybkov, Serhii; Chornobai, Kateryna (My University, 2018)
The use of the created system of biometric identification is very broad and focused on state and commercial facilities with limited funding, such as kindergartens, schools, universities, hospitals, etc. One of the directions of using this system is its use for authentication in modern web-applications and for access to commercial wireless local area networks Wi-Fi, which will become an additional protection against unauthorized access.
Keywords: Wi-Fi; інформаційна система; ідентифікація; додаток; информационная система; идентификация; приложение; information system; identification; application; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки